Dive into the world of knowledge and get your queries resolved at IDNLearn.com. Our experts provide timely and precise responses to help you understand and solve any issue you face.

Use the quadratic formula to solve for X.
2x- + 6x= -3
Round your answer to the nearest hundredth.
If there is more than one solution, separate them with commas.


Sagot :

Answer:

x = 0.75 and or x = -0.38

Step-by-step explanation:

If the minus sign after the x was on purpose or if you accidentally put the addition sign after the minus or the other way around basically I have no idea if the solution I provided is correct so here's the solution to both possible equations you might have meant to type instead (and if this was intentional then awesome):

1. 2x - 6x = -3 and 2. 2x + 6x = -3

Let's do 1. first!

[tex]2x-6x=-3[/tex]

Simplify 2x-6x to -4x

[tex]-4x=-3[/tex]

Divide each side by -4

[tex]x=\frac{-3}{-4}[/tex]

And as you know, two negatives equal/make a positive

[tex]x=\frac{3}{4}[/tex] or [tex]x=0.75[/tex]

Now! Let's solve for 2.

[tex]2x+6x=-3[/tex]

Simplify 2x+6x to 8x

[tex]8x=-3\\[/tex]

Divide both sides by 8

[tex]x=\frac{-3}{8}[/tex]

[tex]x=-\frac{3}{8}[/tex] or [tex]x=-0.375[/tex]